Research-Based Teaching E-Modules on Mangrove Diversity to Enhance Meaningful Learning in Banggai Regency - Moh. Fahri Haruna; Almira Rayyah Shadriah Fahru; Siti Marwah S; Abubakar Sidik Katili; Abdul Haris Odja (Postgraduate, University of Mataram, 2025)
The importance of mangrove ecosystems such as shoreline buffers, biodiversity habitats, and carbon sinks is increasingly threatened by anthropogenic degradation. This study aimed to develop and validate a meaningful learning–based e-module relevant to the context of mangrove diversity in Banggai Regency. Mangrove diversity was utilized as teaching material in the developed e-learning module to provide students with early knowledge about mangroves, enabling them to protect and conserve mangrove ecosystems in their environment. The method employed was a three-stage Research and Development (R&D) approach: field exploration, e-module development based on field data and meaningful learning principles, and product validation by subject matter experts, media experts, and practitioners through observations and questionnaires. Data were analyzed using descriptive qualitative and quantitative methods. The results showed that this interactive e-module, through a limited trial involving 30 students, achieved an average feasibility score of 89.7%. The discussion confirmed that the application of meaningful learning principles integrated with local contexts proved highly valid and effective in improving students' understanding of mangrove diversity. In conclusion, this e-module is feasible and can be implemented to support conservation efforts and enhance students’ understanding. (The total word count is approximately 145, which is concise and covers all essential elements).